PRIVATE EDUCATIONAL SERVICES IN AREA OF PRIMARY EDUCATION IN UKRAINE AS VARIANT OF PREPARATION OF UNIVERSITY ENTRANTS FOR INSTITUTES OF HIGHER - L. Krasovska (Academy of Cognitive and Natural Sciences, 2022)
The question of design-education in the specialized child's educational establishments of culture, which can be base on preparation of university entrants for the designer faculties of institutes of higher, is considered in the article. An author gives the suggestions on permission of problem by specialists on bases of private pedagogical activity in the conditions when the state financing is absent.